Dietary administration of β-caryophyllene and its epoxide to Sprague-Dawley rats for 90 days. (January 2020) - Bastaki, Maria; Api, Anne Marie; Aubanel, Michel; Bauter, Mark; Cachet, Thierry; Demyttenaere, Jan C.R.; Diop, Maodo Malick; Harman, Christie L.; Hayashi, Shim-mo; Krammer, Gerhard; Lu, Vivian; Marone, Palma Ann; et al.
Abstract: Two independent 90-day GLP-compliant studies were conducted in Sprague-Dawley rats with β -caryophyllene or β -caryophyllene epoxide, two common flavoring and fragrance materials. Dietary concentrations of β -caryophyllene were 3500; 7000; and 21, 000 ppm for males and 3500; 14, 000; and 56, 000 ppm for females. Dietary concentrations of β -caryophyllene epoxide were 1750; 10, 500; and 21, 000 ppm. There were no deaths or clinical toxicity attributable to either substance administration. Statistically significant, dose-dependent reductions in body weight, body weight gain, food consumption, and food efficiency at the highest dietary concentrations of β -caryophyllene, but not of β -caryophyllene epoxide, were attributed to palatability issues. Neither β -caryophyllene nor β -caryophyllene epoxide influenced estrus cyclicity or sperm parameters. Macroscopic and microscopic findings were primarily related to changes in the kidneys of male rats, consistent with α2u-globulin nephropathy, and in the liver of male and female rats, including hepatocyte hypertrophy at the middle and high intake levels. These changes correlated with increased absolute and relative organ weights. Since the kidney findings were a species- and sex-specific effect, the NOAEL in each study was based on hepatocyte hypertrophy at the two highest dietary concentrations and were determined to be 222 mg/kg bw/day for β -caryophyllene and 109 mg/kg bw/day for β -caryophyllene epoxide. Highlights: Two 90-day GLP-compliant studies on β -caryophyllene and β -caryophyllene epoxide following OECD guidelines. β -Caryophyllene produces no adverse effects in rats fed at doses up to 222 mg/kg bw/day for 90 days. β -Caryophyllene epoxide produces no adverse effects in rats fed at doses up to 109 mg/kg bw/day for 90 days.